Dry Matter Intake and Growth Performance of Post weaned Nellore lambs Supplemented with Moringa oleifera Leaf meal - D. Sivala; K.C. Matha; R K. Konka; V.S. Chappidi (Indian Journal of Animal Nutrition, 2024)
The effect of incorporation of Moringa oleifera leaf meal(MOLM) on growth performance and dry matter intake of post weaned Nellore lambs as replacement to traditional protein supplements used in concentrate diets was investigated in a completely randomized design experiment using eighteen Nellore lambs with average initial weight of 11.70 kg. There were three treatments T0, T1 and T2 with 0, 15 and 30% MOLM inclusion levels, respectively. MOLM had better nutrient profile with 20.94% Crude protein, 16.85% Crude fibre, 5.70% Ether Extract, 42.50% Nitrogen free extract and 12% ash contents. Incorporation of MOLM as protein supplement significantly increased (P< 0.05) DMI especially at higher (30%) inclusion rates.The final body weights were 16.71±0.22, 17.58±0.17and 17.84±0.20 kg in groups T0, T1 and T2, respectively with significant (P < 0.05) difference between control group and MOLM supplemented groups (15% and 30% levels). The average total weight gain and average daily gain were significantly higher in T2 group. It was concluded that MOLM could be a replacer of traditional protein supplements used in concentrate diets for feeding growing Nellore lambs.